Silver Island Film for Enhancing Light Harvesting in Natural Photosynthetic Proteins - Kowalska, Dorota; Szalkowski, Marcin; Sulowska, Karolina; Buczynska, Dorota; Niedziolka-Jonsson, Joanna; Jonsson-Niedziolka, Martin; Kargul, Joanna; Lokstein, Heiko; Mackowski, Sebastian (International journal of molecular sciences, 2020)
The effects of combining naturally evolved photosynthetic pigment-protein complexes with inorganic functional materials, especially plasmonically active metallic nanostructures, have been a widely studied topic in the last few decades. Besides other applications, it seems to be reasonable using such hybrid systems for designing future biomimetic solar cells. In this paper, we describe selected results that point out to various aspects of the interactions between photosynthetic complexes and plasmonic excitations in Silver Island Films (SIFs). In addition to simple light-harvesting complexes, like peridinin-chlorophyll-protein (PCP) or the Fenna-Matthews-Olson (FMO) complex, we also discuss the properties of large, photosynthetic reaction centers (RCs) and Photosystem I (PSI)-both prokaryotic PSI core complexes and eukaryotic PSI supercomplexes with attached antenna clusters (PSI-LHCI)-deposited on SIF substrates.
Keywords: Photosynthesis; Carotenoids; Spectrometry, Fluorescence; formaldehyd; photosynthetic complexes; fotosystém I (proteinový komplex); Light-Harvesting Protein Complexes; fluorescenční spektrometrie; Nanostructures; karotenoidy; Silver; glukosa; nanostruktury; chlorofyl a; stříbro; Photosystem I Protein Complex; biohybrid structures; Glucose; světlosběrné proteinové komplexy; Chlorophyll A; SIF; fotosyntéza; MEF; Formaldehyde